2017
DOI: 10.1074/mcp.m116.066746
|View full text |Cite
|
Sign up to set email alerts
|

Paucimannose-Rich N-glycosylation of Spatiotemporally Regulated Human Neutrophil Elastase Modulates Its Immune Functions*.

Abstract: Human neutrophil elastase (HNE) is an important -glycosylated serine protease in the innate immune system, but the structure and immune-modulating functions of HNE-glycosylation remain undescribed. Herein, LC-MS/MS-based glycan, glycopeptide and glycoprotein profiling were utilized to first determine the heterogeneous -glycosylation of HNE purified from neutrophil lysates and then from isolated neutrophil granules of healthy individuals. The spatiotemporal expression of HNE during neutrophil activation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 116 publications
(133 reference statements)
6
85
1
Order By: Relevance
“…Paucimannosylation is a common modification of proteins expressed by lower organisms, but our recent reports indicate that higher organisms including humans also express paucimannosidic proteins albeit in a more tissue‐restricted and physiology‐dependent manner . Paucimannosylation appears particularly central to the human innate immune system as supported by our previously published data documenting that PMGs are carried by biologically important proteins still displaying bioactivity and structural integrity expressed by resting and activated human neutrophils and macrophages . The findings presented herein documenting that PMGs also serve as signatures of human cancers add to our knowledge of this understudied N ‐glycan type, but at the same time prompts several questions, some of which are discussed below to encourage and stimulate further activity in this research field.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Paucimannosylation is a common modification of proteins expressed by lower organisms, but our recent reports indicate that higher organisms including humans also express paucimannosidic proteins albeit in a more tissue‐restricted and physiology‐dependent manner . Paucimannosylation appears particularly central to the human innate immune system as supported by our previously published data documenting that PMGs are carried by biologically important proteins still displaying bioactivity and structural integrity expressed by resting and activated human neutrophils and macrophages . The findings presented herein documenting that PMGs also serve as signatures of human cancers add to our knowledge of this understudied N ‐glycan type, but at the same time prompts several questions, some of which are discussed below to encourage and stimulate further activity in this research field.…”
Section: Discussionsupporting
confidence: 55%
“…However, it is likely that the PMGs identified from proteins extracted from the tumor tissues originate from multiple cell types including directly from the cancer cells as well as from the cancer‐associated stroma, adipocytes, immune cells, and necrotic cells forming the heterogeneous tumor micro‐environment . In support, M2Fa and to a lesser extent M3Fa, which in this study were found to be key PMGs of the tumor tissues, have repeatedly been reported to be abundant glycans carried by proteins expressed by neutrophils and macrophages . Neutrophils and macrophages are important innate immune cells that are known to reside in and modulate the tumor micro‐environment as tumor‐associated neutrophils (TANs) and macrophages (TAMs) .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Differences in primary structure do not account for the observed differences in N-glycan processing: the CD16a polypeptide sequence and presence of the coexpressed Fc e receptor g-chain were the same in both NK cells and that used in HEK293F cells to express frCD16a. Cell-type specific differences in the glycosylation of a specific protein are known (40)(41)(42)(43)(44) and are justifiable given the complexity of gene expression and activity for glycan-processing enzymes in different tissues (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%